Modelling the costs and benefits of breeding programmes using crop wild relatives reveals high potential returns - Drucker, Adam G.; Grazioli, Francesca; Brehm, Joana M.; Maxted, Nigel; Dulloo, Mohammad Ehsan (2022)
Crop improvement strategies rely on a continued supply of genetic diversity and associated beneficial traits, of which crop wild relatives (CWR) are a major source. They provide cultivars with pest and disease resistance, heat and drought tolerance, tolerance of salinity and other abiotic stresses, and enhanced nutritional quality. It has been estimated that approximately 30% of modern crop production increase is due to the use of CWR genetic diversity.